Meeting in the Middle: Future Directions for Researchers to Support Educators' Assessment Literacy and Data-Based Decision Making - Will, Kelsey K.; McConnell, Scott R.; Elmquist, Marianne; Lease, Erin M.; Wackerle-Hollman, Alisha (Frontiers in Education, 2019)
Assessment is prevalent throughout all levels of education in the United States. Even though educators are familiar with the idea of assessing students, familiarity does not necessarily ensure assessment literacy or data-based decision making (DBDM) knowledge. Assessment literacy and DBDM are critical in education, and early childhood education in particular, to identify and intervene on potential barriers to students’ development. Assessment produces data and evidence educators can use to inform intervention and instructional decisions to improve student outcomes. Given this importance and educators’ varying levels of assessment literacy and DBDM knowledge, researchers and educators should be willing to meet in the middle to support these practices and improve student outcomes. We provide perspective for half of the equation– how researchers can contribute– by addressing important considerations for the design and development of assessment measures, implications of these considerations for future measures, and a case example describing the design and development of an assessment tool created to support DBDM for educators in early childhood education.